Research progress of functional motifs based on growth factors in cartilage tissue engineering: A review - Qin, Shengao; Zhu, Jiaman; Zhang, Guangyong; Sui, Qijia; Niu, Yimeng; Ye, Weilong; Ma, Guowu; Liu, Huiying (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis is a chronic degenerative joint disease that exerts significant impacts on personal life quality, and cartilage tissue engineering is a practical treatment in clinical. Various growth factors are involved in cartilage regeneration and play important roles therein, which is the focus of current cartilage repair strategy. To compensate for the purification difficulty, high cost, poor metabolic stability, and circulating dilution of natural growth factors, the concept of functional motifs (also known as mimetic peptides) from original growth factor was introduced in recent studies. Here, we reviewed the selection mechanisms, biological functions, carrier scaffolds, and modification methods of growth factor-related functional motifs, and evaluated the repair performance in cartilage tissue engineering. Finally, the prospects of functional motifs in researches and clinical application were discussed.